Structural disconnectivity from paramagnetic rim lesions is related to disability in multiple sclerosis. Issue 10 (8th September 2021) - Tozlu, Ceren; Jamison, Keith; Nguyen, Thanh; Zinger, Nicole; Kaunzner, Ulrike; Pandya, Sneha; Wang, Yi; Gauthier, Susan; Kuceyeski, Amy
Abstract: Background: In people with multiple sclerosis (pwMS), lesions with a hyperintense rim (rim+) on Quantitative Susceptibility Mapping (QSM) have been shown to have greater myelin damage compared to rim‐ lesions, but their association with disability has not yet been investigated. Furthermore, how QSM rim+ and rim‐ lesions differentially impact disability through their disruptions to structural connectivity has not been explored. We test the hypothesis that structural disconnectivity due to rim+ lesions is more predictive of disability compared to structural disconnectivity due to rim‐ lesions. Methods: Ninety‐six pwMS were included in our study. Individuals with Expanded Disability Status Scale (EDSS) <2 were considered to have lower disability (n = 59). For each gray matter region, a Change in Connectivity (ChaCo) score, that is, the percent of connecting streamlines also passing through a rim‐ or rim+ lesion, was computed. Adaptive Boosting was used to classify the pwMS into lower versus greater disability groups based on ChaCo scores from rim+ and rim‐ lesions. Classification performance was assessed using the area under ROC curve (AUC). Results: The model based on ChaCo from rim+ lesions outperformed the model based on ChaCo from rim‐ lesions (AUC = 0.67 vs 0.63, p ‐value < .05). The left thalamus and left cerebellum were the most important regions in classifying pwMS into disability categories. Conclusion: rim+ lesions may be more influential on disability through their disruptions to the structural connectome than rim‐ lesions. This study provides a deeper understanding of how rim+ lesion location/size and resulting disruption to the structural connectome can contribute to MS‐related disability. Abstract : The hyperintense rim lesions on Quantitative Susceptibility Mapping (QSM) (QSM rim+ lesions) have been shown to be particularly detrimental to tissue concentration causing greater myelin damage compared to chronic silent lesions (QSM rim‐ lesions) in multiple sclerosis (MS). However, there is no large study to date that has demonstrated the relationship of disability with rim+ lesions that are identified with QSM in MS. Our results showed that structural disconnectivity associated with rim+ lesions on QSM was more related to disability than structural disconnectivity associated with rim‐ lesions. Damages to the structural connections of the left cerebellum and thalamus from either lesion type were especially impactful on disability. This analysis provides a deeper understanding of how different lesion types can disrupt the structural connectome and contribute to MS‐related disability. A deeper understanding of the role of the connectome in MS is needed if we are to gain a comprehensive view of the disease to ultimately improve clinical outcomes in people with MS.